Design of a mechanism to mix biogas with air in compression internal combustion engine - Ahmad Hazury, Hamid (2010)
Internal combustion engines burn fuel to create kinetic energy. The burning of fuel is basically the reaction of the fuel with the oxygen in the air. The amount of oxygen present in the cylinder is the limiting factor for the amount of fuel can be burnt. If there’s too much fuel present, not all fuel will be burnt and un-burnt fuel will be pushed out through the exhaust valve. When building an engine, it’s very important to know the air-fuel ratio at which exactly all the available oxygen is used to burn the fuel and all the fuel is burnt completely. This ratio is called the stoichiometric air-fuel ratio. This project has successfully design a venturi mixer and analyze design of pressure regulator that perform accurate state estimation achieving desired outputs with certain parameters setting. It helps identify the current operating state of the system on which, on certain condition can generate the accurate output.